The Calculation and Allocation of Marine Environmental Capacity for Daya Bay Under the Policy of Total Waste Load Control - Jiang, Jingyuan (My University, 2009)
The system of total waste load control (TWLC) has been developed and implemented in China since 1980s. Environmental capacity is the most important concept of TWLC system and its calculation and allocation are the bases to set TWLC targets and to make pollutants reduction schemes. In 2008, Guangdong Provincial Oceanic and Fishery Administration (GPOFA) proposed the TWLC strategy for ocean based on the scientific evaluation of marine environmental capacity. Daya bay, a semi-enclosed bay located in the south of Guangdong Province was selected as the research objective. In this thesis, the environmental capacities of Daya Bay in terms of chemical oxygen demand (CODcr), nitrogen existed as ammonia (NH3-N) and reactive phosphate (PO4-) are calculated and allocated to the administrative districts located in Daya Bay’s catchment basin. By combining the accounting and prediction results of pollutants discharge amounts, total waste load control and reduction schemes are developed.
Keywords: Miljöteknik; Environmental engineering